Collaborative Behaviour as a Facilitator of Integration of Logistic and Marketing Functions – The Case of Slovene Retailers - Topolšek, Darja; Čižman, Anton; Lipičnik, Martin (Promet - Traffic&Transportation, 2012)
Collaborative behaviour and various aspects of comparing collaboration with coordination and cooperation present the basis for more detailed assumptions concerning the importance of integrating logistic function with the marketing function. The collaborative behaviour dimension of inter-functional integration presents a system of mutual visions, decision-making and collective responsibility to provide results, services or a product. Logisticians often define integration within the framework of the supply chain, yet they neglect the internal integration or the integration between individual departments or functions in a company. Defining internal integration and its level as well as the connection with the level of collaborative behaviour is the basis of the research part of this paper. The quantitative research part studies whether and to what extent collaborative behaviour influences the level of internal integration between logistic and marketing functions. The research is based on a quantitative analysis of results of the survey that was conducted in Slovene retail companies.KEY WORDS: logistics, marketing, logistic function, marketing function, internal integration, collaborative behaviour, inter-functional relations